2011
DOI: 10.1152/ajpendo.00011.2011
|View full text |Cite
|
Sign up to set email alerts
|

Maternal prenatal undernutrition programs adipose tissue gene expression in adult male rat offspring under high-fat diet

Abstract: -Several studies have shown that maternal undernutrition leading to low birth weight predisposes offspring to the development of metabolic pathologies such as obesity. Using a model of prenatal maternal 70% food restriction diet (FR30) in rat, we evaluated whether postweaning high-fat (HF) diet would amplify the phenotype observed under standard diet. We investigated biological parameters as well as gene expression profile focusing on white adipose tissues (WAT) of adult offspring. FR30 procedure does not wors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
95
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(116 citation statements)
references
References 64 publications
(103 reference statements)
17
95
2
1
Order By: Relevance
“…In particular, FR30N rats exhibited increased expression of several genes associated with de novo lipogenesis whereas no difference was observed in gene expression levels for gene involved in adipogenesis. 3 Our findings mirror the WAT transcriptional pattern described in a rat model of maternal protein restriction (MPR) throughout gestation and lactation. 7 In line, maternal 50% food restriction from 10 d to term gestation leads to adult intrauterine growth-restricted male rats that exhibited programmed upregulation of adipogenic transcription factor leading to hypertrophic adipocytes.…”
Section: Does Maternal Undernutrition Predispose Adult Offspring To Asupporting
confidence: 75%
See 1 more Smart Citation
“…In particular, FR30N rats exhibited increased expression of several genes associated with de novo lipogenesis whereas no difference was observed in gene expression levels for gene involved in adipogenesis. 3 Our findings mirror the WAT transcriptional pattern described in a rat model of maternal protein restriction (MPR) throughout gestation and lactation. 7 In line, maternal 50% food restriction from 10 d to term gestation leads to adult intrauterine growth-restricted male rats that exhibited programmed upregulation of adipogenic transcription factor leading to hypertrophic adipocytes.…”
Section: Does Maternal Undernutrition Predispose Adult Offspring To Asupporting
confidence: 75%
“…We then investigated tissue gene expression profile focusing on the WAT programmed mechanisms. 3 Most of the following results have been recently published.…”
mentioning
confidence: 99%
“…Maternal reduced nutrition programmes an increase of fat cell size and number in the offspring. Adult rat offspring from LP dams (Guan et al 2005) and from FR70 dams during gestation (Lukaszewski et al 2011) showed enhanced adipogenesis (i.e. elevated PPARG activity) with impaired leptin antilipogenic action.…”
Section: Maternal Reduced Nutritionmentioning
confidence: 99%
“…Support for this hypothesis has been provided by several studies. In rats, maternal undernutrition changed the gene expression profile that predisposes to altered fat deposition [6], whereas signs of increased oxidative stress and fibrosis were discovered in pancreatic islets in offspring of protein-restricted pregnant rats [7]. However, whether the association between early life factors and the development of type 2 diabetes is due to fetal programming or underlining common genetic and environmental influence remains debatable.…”
Section: Introductionmentioning
confidence: 99%